THE USE OF READING PORTFOLIO IN DEVELOPING LEARNER AUTONOMY : A Mixed Method Study at a Vocational High School in West Java - Fitri Aprianti, - (2018)
Learner autonomy has been listed as one of the core competencies in the recent curriculum of 2013. Accordingly, this study is intended to explore the use of reading portfolio in developing learner autonomy in vocational high school level. The study employed a mixed method approach with a quasi-experimental and qualitative interview designs. The population involved in the study were 440 students of a vocational high school in West Java, two classes were assigned as experimental and control groups, and five students from the experimental group were assigned as respondents of the interviews. The data were collected by using inventory tests (pretest-posttest), portfolio documents, and interviews. The three principles for promoting learner autonomy development, namely learner involvement, learner reflection, and target language use were used as the basis design to analyse the data gathered. The results of the inventory test (pretest) show that the profile of initial autonomy development of the population was moderate. The moderate profile of learner autonomy development indicates that the students had not yet reached the optimum capacity to carry active involvement, reflection, and target language use in reading. Accordingly, the findings signify that a type of preventive intervention is needed so that learner autonomy can be developed. Whereas, the results of the preventive intervention (the experimental study) reveal that the experimental group could show better improvement than that of the control group in terms of the learner autonomy development. This finding implies that the students who received the reading portfolio could better develop their capability to get involved, reflect, and use target language more in reading. Lastly, the students' responses on the use of reading portfolio signal that the students had relatively positive attitude on the use of the reading portfolio in developing their autonomy in reading. Finally, it is recommended that educational practitioners can use the reading portfolio to develop learner autonomy.